The Unauthorized Residency Status Myth: Health Insurance Coverage and Medical Care Use among Mexican Immigrants in California - Enrico A. Marcelli (Migraciones Internacionales, 2004)
Informed by recent developments in the behavioral model of medical care use and social epidemiology, this article employs survey data to estimate whether unauthorized residency status among non elderly Mexican and other-Latino immigrant adultsin California influenced the probability of having had health insurance and havingreceived medical care. Unauthorized residency status is estimated to have decreased the probability of having been insured, and augmented the probability of havingrelied on public health insurance. However, after controlling for other individual characteristics, neighborhood context, and social capital, neither insurance nor residency status appears to have influenced whether a person obtained needed medicalcare. Rather, neighborhood context, difficulty locating a medical care facility, andcivic engagement appear to be more important for understanding use of medical services.